Health Behaviors Enhancing Based on Local Wisdom - พงษ์ศักดิ์ชาติ พเยาว์; มาลัย ชุติมา; น้อยสีภูมิ นิตติยา; จำปาเทศ มนัสวี (Journal of The Royal Thai Army Nurses, 2019)
Health behavior refers to individuals’ performances that affect all aspects of their health. The effects can be either positive effects or negative effects.This article aims to present methods to enhance people’s health behaviors based on local wisdoms. Results found that health behaviors based on local wisdoms each region yielded the following : Per food consumptions, consume local vegetables and fruits were rich in vitamins , minerals and herbal benefits. For the exercise, apply local dances, occupational gestures, and materials in local area to design proper exercises. Lastly, coping behavior, use folk music and performances including religious teachings for emotional control or relaxation. Health behaviors enhancing based on local wisdoms include health education, training program, integration of learning content to increase awareness of the value of local wisdoms and applied appropriately for health benefits.